PENGARUH KONSEP DIRI KRISTEN GURU PAK TERHADAP FORMASI KONSEP DIRI KELAS VIII SMP NEGERI 2 PORSEA TOBASA TAHUN 2017/2018 - Meilan Pakpahan (IAKN Tarutung, 2018)
Abstract, This research intent to know Concept influence Self Christian Subject Teacher to Formation Concept Self Student’s at SMP N 2 Porsea Toba Samosir's Regencies Academic Year 2017 / 2018. Observational hypothesis is: available influence which signifikan among Concept Self Christian Subject Teacher to Formation Concept Self VIII class Student’s SMP Country 2 Porsea Toba Samosir's Regencies Academic Year 2017 / 2018. Observational method is inferensial's statistical methods. Exhaustive observational VIII class student’s SMP Country 2 Porsea Academic Year 2017 / 2018 totals 218 student’s. Sample is taken 25% of each classes which is 56 student’s. Observational instrument that is utilized is enclosed questionnaire. Analisis's result assesses r xy = 0,255 r tab = 0,226 and t ob = 1,938 t tab = 1,671 point out that mark sense relationship and significance among Concept Self Christian Subject Teacher to Formation Concept Self Student’s and gets simple regression equation significance which is Ŷ = 35,717 = + 0,378X. Hypothesis quiz is gotten F ob =46,141 F tab =1,51 therefore h0 refused and ha accepted. This research concludes that Concept Self Christian Subject Teacher regard Concept Forming Self Student’s as big as 6,502%. Keywords : Concept Self Christian Subject Teacher, Formation Concept Self Student’s